EFFECTIVE TUTORING: LEARNERS’ PERCEPTION AND INSTITUTIONAL RESPONSIBILITY: Prakash Arumugam (PJDOL, 2023)
AOne of the key elements of the open and distance learning (ODL) is the face-to-face component that is embedded in the delivery system. Due to the sheer geographical reach of an ODL institution, the use of lectures is not feasible. Therefore, most ODL institutions rely on tutors appointed according to regions to deliv